2020
DOI: 10.3389/fimmu.2020.589929
|View full text |Cite
|
Sign up to set email alerts
|

TERT—Regulation and Roles in Cancer Formation

Abstract: Telomerase reverse transcriptase (TERT) is a catalytic subunit of telomerase. Telomerase complex plays a key role in cancer formation by telomere dependent or independent mechanisms. Telomere maintenance mechanisms include complex TERT changes such as gene amplifications, TERT structural variants, TERT promoter germline and somatic mutations, TERT epigenetic changes, and alternative lengthening of telomere. All of them are cancer specific at tissue histotype and at single cell level. TERT expression is regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
138
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(165 citation statements)
references
References 210 publications
(291 reference statements)
1
138
0
3
Order By: Relevance
“…These mutations result in a new consensus binding site for E-twenty-six (ETS) transcription factors and this may contribute to increased TERT . The ETS transcription factors are downstream targets of the RAS-RAF-MAPK pathways, and TERT promoter mutations are suggested to have synergistic effects with activating BRAF or NRAS mutations to promote tumor cell proliferation [ 21 ]. TERT is involved in the AKT pathway, and plays an important role in cellular immortality [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mutations result in a new consensus binding site for E-twenty-six (ETS) transcription factors and this may contribute to increased TERT . The ETS transcription factors are downstream targets of the RAS-RAF-MAPK pathways, and TERT promoter mutations are suggested to have synergistic effects with activating BRAF or NRAS mutations to promote tumor cell proliferation [ 21 ]. TERT is involved in the AKT pathway, and plays an important role in cellular immortality [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…TERT mRNA overexpression does not completely explain all effects of the TERT promoter mutations in tumorigenesis, and the role of immunohistochemistry in determining the TERT status is still a topic of debate [ 22 ]. Consequently, other undefined or epigenetic mechanisms of TERT -upregulating are expected to exist [ 21 , 23 , 24 ]. While a TERT promoter mutation is not found in conjunctival nevi, it is found in both PAM [ 14 ] and CM [ 6 , 14 ], with increased TERT expression leading to tumor progression [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also demonstrated STAT3 activation by hypoxia to be essential for the acquisition of survival and functional benefits of NK cells. STAT3 is known to be an activator of human telomerase reverse transcriptase (hTERT) [ 45 ], and NK cell senescence from mbIL15-mediated expansion can be restored with hTERT gene modification. Since our data showed a reduction in the expression of p21/p53 tumor suppressors [ 46 ], along with a concomitant decrease in p16 mRNAs (data not shown) in hypoxia-exposed NK cells, inhibition of senescence by promoting hTERT activity could also have contributed to the increase in NK cells beyond 20 days of ex-vivo hypoxic NK culture.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results indicate that TERT determines the cancerous function of mutant MEG3. Telomerase, an RNA-dependent DNA polymerase with telomerase reverse transcriptase (TERT), regulates cancer formation (54,55).A particular attention is given to the putative connections between TERT transcriptional reactivation and signalling pathways frequently altered in cancer, such as c-MYC, NF-κB and β-Catenin(56). TERT promoter mutations are associated with poor prognosis and cell immortalization in meningioma (57).DNA methylation of the TERT promoter is associated with human cancer(58).TERT and TERC mutations suppress telomerase activity (59).TERT C228T mutation is associated with intravesical recurrence for patients with non-muscle invasive bladder cancer(60).TERC is an RNA component of telomerase and TERC promotes cellular in ammatory response independent of telomerase(61).…”
Section: Discussionmentioning
confidence: 99%